What Drives Credit Growth in Emerging Asia? - Han, Fei (IMF Working Papers; Working Paper, 2012)
This paper seeks to uncover the main drivers of credit growth in emerging Asia using a multi-country structural vector autoregressive (SVAR) model. Taking a novel approach, we developed a two-block SVAR whereby shocks within blocks are identified using sign restrictions, whereas shocks across the blocks are identified using a recursive (block-) Cholesky structure. We find that domestic factors are more dominant than external factors in driving rapid credit growth in emerging Asia. This is particularly true for domestic monetary policy, which can play a pivotal role in terms of managing rapid credit growth in emerging Asia.